2017
DOI: 10.1093/hcre.12111
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Media Multitasking and Attention Problems in Adolescents: Results of Two Longitudinal Studies

Abstract: The increased prevalence of media multitasking among adolescents has raised concerns that media multitasking may cause attention problems. Despite cross-sectional evidence of the relationship between media multitasking and attention problems, no study has yet investigated this relationship longitudinally. It is therefore unclear how these two variables are related. Two 3-wave longitudinal studies with 3-and 6-month time lags were conducted. In total, 2,390 adolescents aged 11-16 provided data on media multitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 50 publications
2
47
1
1
Order By: Relevance
“…Furthermore, both the immediate and chronic effects of media multi‐tasking are relatively unexplored in children and adolescents, who are the prime users of such technologies and are at a phase of development that is crucial for refining higher cognitive abilities. The first longitudinal study of media multi‐tasking in young people has recently found that frequent multi‐tasking behaviours do predict the development of attentional deficits specifically in early adolescents, but not in older teens. Additionally, extensive media multi‐tasking during childhood and adolescence could also negatively impact cognitive development through indirect means, by reducing engagement with academic and social activities, as well as by interfering with sleep, or reducing the opportunity to engage in creative thinking.…”
Section: “Digital Distractions”: a Hijack Of Attention On The Informamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both the immediate and chronic effects of media multi‐tasking are relatively unexplored in children and adolescents, who are the prime users of such technologies and are at a phase of development that is crucial for refining higher cognitive abilities. The first longitudinal study of media multi‐tasking in young people has recently found that frequent multi‐tasking behaviours do predict the development of attentional deficits specifically in early adolescents, but not in older teens. Additionally, extensive media multi‐tasking during childhood and adolescence could also negatively impact cognitive development through indirect means, by reducing engagement with academic and social activities, as well as by interfering with sleep, or reducing the opportunity to engage in creative thinking.…”
Section: “Digital Distractions”: a Hijack Of Attention On The Informamentioning
confidence: 99%
“…For instance, the Internet's digital distractions and supernormal capacities for cognitive offloading seem to create a non‐ideal environment for the refinement of higher cognitive functions in critical periods of children and adolescents’ brain development. Indeed, the first longitudinal studies on this topic have found that adverse attentional effects of digital multi‐tasking are particularly pronounced in early adolescence (even compared to older teens), and that higher frequency of Internet use over 3 years in children is linked with decreased verbal intelligence at follow‐up, along with impeded maturation of both grey and white matter regions.…”
Section: Conclusion and Directionsmentioning
confidence: 99%
“…The meta-analysis covers a period of more than 25 years, the earliest data was collected in 1990 (Forschungsgruppe Wahlen et al, 2013), and the latest panel started in 2017 (Roßteutscher et al, 2018). Baumgartner et al (2017) 2016 NL Adolescents online 3 919 32 Baumgartner et al (2017) 2016 NL Adolescents online 2 397 33 Roßteutscher et al (2018) 2017 DE Adults online 11 9531…”
Section: Methods Samplementioning
confidence: 99%
“…Only (sub-)samples with more than 50 respondents per measure were included in order to obtain stable estimates. Among the analyzed data sets are well-known studies such as the General Social Survey, the American National Election Study (ANES) or the German Longitudinal Election Study (GLES, Rattinger, Roßteutscher, Schmitt-Beck, Weßels, & Steinbrecher, 2015), but also data from diverse media exposure and effects studies (Baumgartner, van der Schuur, Lemmens, & te Poel, 2017;Quandt, Festl, Breuer, Scharkow, & Kowert, 2017), consumer panels (Wonneberger & Irazoqui, 2017) or previously unpublished project data. 1 Most studies in the sample were conducted in either Germany (n = 11) or the Netherlands (n = 10), followed by the United 1 The references for unpublished data contain some information about the sample and data collection, but might not discuss the media exposure measures at all.…”
mentioning
confidence: 99%
“…Future studies should address these limitations and further examine individual and situational differences in MM behavior. For example, some adolescents may be predisposed to engage in higher levels of MM and this behavior may make them more sensitive to distracting or irrelevant information (Baumgartner, van der Schuur, Lemmens, & te Poel, ). Previous cross‐sectional work suggests that young drivers with executive functioning difficulties and poorer speed of processing abilities are at risk for negative driving outcomes (McManus et al, ; Pope, Ross, & Stavrinos, ).…”
Section: Future Opportunities and Challenges In Media Multitasking Rementioning
confidence: 99%